Identifying the challenges to implementing a neuromuscular warm-up in pre-elite netball - Smyth, E.; Appaneal, R.; Drew, M.; Antcliff, A.; Waddington, G.; Newman, P.; Weissensteiner, J.; Donaldson, A. (International Journal of Sports Science & Coaching, 2021)
Objective: To identify challenges for implementing Netball Australia`s `Knee injury prevention for Netballers and Enhance performance and Extend play` (KNEE) program for 17/U & 19/U State (i.e. regional/provincial representative) teams. Design: Concept mapping, a mixed-methods approach incorporating qualitative and quantitative data collection and analyses. Setting: Pre-elite netball. Participants: Thirty-nine netball coaches, strength & conditioning coaches and physiotherapists working with State 17/U & 19/U teams. Methods: Participants brainstormed challenges to implementing the KNEE program, sorted the challenges into groups based on similar meaning and rated the importance and difficulty of overcoming each challenge on a scale from 0 (least important/easiest to overcome) to 5 (most important/hardest to overcome). Results: Forty-six statements (i.e. challenges) were identified and organised into the following eight clusters (mean importance rating out of 5, mean difficulty rating out of 5): `athlete engagement` (3.31, 2.48); `supervision and correction of technique` (3.03, 2.67); `time constraints` (2.79, 2.59); `athlete technique` (2.70, 2.64); `education` (2.56, 2.16); `support staff resourcing` (2.51, 2.67); `program flexibility and adaptability` (2.02, 1.85); and `coach and support staff prioritisation` (1.95, 1.81). Nineteen statements/challenges had above average ratings for importance (2.63) and difficulty (2.41). Conclusions: This study identified `athlete engagement`, `supervision and correction of technique`, `time constraints`, `athlete technique`, `education` and `support staff resourcing` as the most important and difficult challenges to implementing the KNEE program in pre-elite netball. These multi-factorial challenges are the main barriers to implementing the KNEE program. They can be addressed using the implementation driver`s framework.